Crowding Population-based Ant Colony Optimisation for the Multi-objective Travelling Salesman Problem - Angus, D. (2007 IEEE Symposium on Computational Intelligence in Multi-Criteria Decision Making, Honolulu, HI, 1-5 April 2007, 2007)
Ant inspired algorithms have gained popularity for use in multi-objective problem domains. One specific algorithm, Population-based ACO, which uses a population as well as the traditional pheromone matrix, has been shown to be effective at solving combinatorial multi-objective optimisation problems. This paper extends the population-based ACO algorithm with a crowding population replacement scheme to increase the search efficacy and efficiency. Results are shown for a suite of multi-objective travelling salesman problems of varying complexity